مظاهرات المسلمين ضد بيانات الحكام المضادة للإسلام في ضوء السنة قضية أهوك الإندونيسي أ نموزجا - Ahmad Syauqi (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
The research examines the position of Islam on public mass or social demonstration as a form of protest against the state. It looks into whether there are any historical sources in the Sunnah and Islamic history that may shed some information and understanding in relation to such act. One of the main reasons for the need of such discussion is due to the large discrepancy of views and practices among religious groups, namely extremist group as well as the liberal groups, which has led to a number of conflicts, sometimes violently, for the past few years in the Republic of Indonesia. The extremist group generally holds the view that all forms of demonstration are prohibited, on the basis that such practices are derived from Western culture and is not part of the Islamic tradition. As for the liberal groups, they view public demonstrations as permissible and can be conducted at any place and time without the need for permission or approval from any form of authority. The research is divided into five main chapters. The first being research plan and its general structure. The second is the concept of the demonstration among scholars and its development. The third is the forms of public demonstration during the era of the Prophet (PBUH) and after him. The fourth is the background of the demonstration against the former Governor of Jakarta and its causes, the position of Indonesian law, and the debate between those who support and oppose the demonstration. Finally, the fifth is on opinions and perspectives of scholars in regard to the demonstration and its comparison. The research adopts the inductive, historical and descriptive approaches. The findings of the research illustrate that public demonstration has long existed from the time of the prophet Muhammad (PBUH). The result also reveals that there is a strong evidence for the permissibility of demonstration which is sanctioned by Islamic law as found in its historical root.